HUBUNGAN TIPE KPRIBADIAN DENGAN PENCARIAN SENSASI PADA KONSUMEN IPAD - Lasyitha Anindiya, - (2012)
This study aims to knowing the relationship between personality types and sensation seeking on iPad consumer at Bandung. iPad is an internet-based product designed, developed, and marketed by Apple Inc., where the name's very popular among gadget lovers. Personality types is a personality taxonomy based on the result from individual's natural language analysis which explains himself and other people that gives explanation of personality system generally (John & Srivastava, 1999). Meanwhile, sensation seeking is a trait determined by need for sensation and varies experiences seeking, new and unusual, complex and intense, and the willingness to take physical, social, legal, and financial risks only for having some experiences (Zuckerman, 1979; 1991). Sampling techniques used in this study is the incidental sampling technique. The research conducted by distributing 40 questionnaires to iPad consumer in Bandung. Research method used is quantitative research method with correlational approach. Results obtained from this study is the majority of iPad consumer in Bandung have the openness to experience type's tendency (mean = 3,038) with sensation seeking at intermediate level (35%). Further, based on Pearson Correlation's calculation, showed that only the openness to experience type have a relation with the sensation seeking, with a positive and significant correlation of 0,527. Meanwhile, extraversion, neuroticism, conscientiousness and agreeableness type don't have a significant relation with someone's sensation seeking.